“I don’t see a reason why we should be hidden from view”: Views of a convenience sample of people living with HIV on sharing HIV status data in routinely collected health and care databases in England - Elizabeth Ford; Katie Goddard; Michael Smith; Jaime Vera (PLoS ONE, 2025)
Introduction People living with HIV (PLWH) now have near-normal life-expectancy, but still experience stigma, and HIV status is treated as sensitive health information. When UK healthcare patient data is curated into anonymised datasets for research, HIV diagnostic codes are stripped out. As PLWH age, we must research how HIV affects conditions of ageing, but cannot do so in current NHS research datasets. We aimed to elicit views on HIV status being shared in NHS datasets, and identify appropriate safeguards. Methods We conducted three focus groups with a convenience sample of PLWH recruited through HIV charities, presenting information on data governance, data-sharing, patient privacy, law, and research areas envisaged for HIV and ageing. Each focus group involved two presentations, a question session, and facilitated breakout discussion groups. Discussions were audio-recorded, transcribed and analysed thematically. Results 37 PLWH (age range 23-58y) took part. The overarching theme was around trust, both the loss of trust experienced by participants due to previous negative or discriminatory experiences, and the need to slowly build trust in data-sharing initiatives. Further themes showed that participants were supportive of data being used for research and health care improvements, but needed a guarantee that their privacy would be protected. A loss of trust in systems and organisations using the data, suspicion of data users’ agendas, and worry about increased discrimination and stigmatisation made them cautious about data sharing. To rebuild trust participants wanted to see transparent security protocols, accountability for following these, and communication about data flows and uses, as well as awareness training about HIV, and clear involvement of PLWH as full stakeholders on project teams and decision-making panels. Conclusions PLWH were cautiously in favour of their data being shared for research into HIV, where this could be undertaken with high levels of security, and the close involvement of PLWH to set research agendas and avoid increased stigma.